Development of Universiti Teknologi MARA Sport Center Alumni Database (USCA) using distributed database approach in horizontal fragmentation technique / Norafiza Awalludin - Awalludin, Norafiza (2006)
Universiti Teknologi Mara (UiTM) Sport Center is an organization that responsible to manage, maintain and promote sport services for student and staff. Even their task is more to organize about management of sport but it does not means that they are not able to excel in technologies. With the inspiration from UiTM Sport Center and full support from Head of UiTM Sport Center, Mr. Mustaza Ahmad, they aim to create an Information System to store data about former students that was actively involves in sports as well as those are still have excellent achievement in Malaysian sport. The information system will contain the former student background, sport achievements and career. With this mformation system, it is hope that it will ease the works of capturing information and make it easy to be used by Staff of UiTM Sport Center.